Neonatal oral teratoma: A case report - Moustapha, Helle; Habou, Oumarou; Ousmane, Kadre Alio Kadre; Ada, Mahamoud Omid Ali; Bako, Inoussa Daouda; Effared, Boubacar; Sabo, Ramatou; Abarchi, Habibou (Journal of Neonatal Surgery, 2021)
Background: Teratomas of the oral cavity are rare and can pose danger to a patient's life in terms of obstruction to the aerodigestive tract. These are the germ cell tumors that arise from all three layers of primordial germ cells. Case Presentation: A 2-day-old female neonate presented with a mass protruding from the oral cavity since birth with no significant antenatal history. Examination revealed a large (8 cm), firm, and irregular mass protruding from the oral cavity extending up to the inner surface of the upper lip and onto the gums, associated with cleft palate. Complete excision of the mass was done and histopathology confirmed the diagnosis. There were no postoperative complications. Conclusion: Oral cavity teratoma is a rare tumor with a good prognosis especially in its mature form. Surgical excision with multidisciplinary collaboration is needed in order to avoid any complications.